Les écrivains communistes pour la jeunesse pendant l’entre-deux-guerres - Mathilde Lévêque (Itinéraires)
After the First World War, communist writers participate in a novel impetus towards the reflexion about and the creation of children literature. As engaged militants and fellow travelers, these writers create new heroes that fight against capitalism and work for peace or for the liberation of colonised people. In their innovative books, translation and cultural exchange play moreover an important dynamical role.